Study on a multi-satellite constrained space-time anti-jam algorithm - Guo-sheng HUANG; Zheng-rong YI; Tao SHUAI; Zhen-cai ZHU (Tongxin xuebao)
A multi-satellite constrained space-time anti-jam algorithm was proposed for global navigation satellite system(GNSS)receivers.Firstly the equivalent GSC structure of multi-satellite constrained LCMV principle was considered and its forward decomposition process was simplified and improved,so the computation complexity was reduced to approach single-satellite constrained problem.Then the Householder multi-stage Wiener filtering(MWF)algorithm was proposed to solve the classical Wiener filtering problem in the GSC structure,and an efficient order-recursive implementation structure was obtained by improving the backward recursive process using the decomposition property of MWF,so the real-time performance was greatly promoted and the reduced rank could be adaptively estimated from the output of MSE.The complete procedure of the proposed algorithm is summed up and its validation is verified by simulations.